Extensive Longitudinal Transverse Myelitis after Influenza A Virus Infection in a Patient with Systemic Lupus Erythematosus - Márquez, Suheiry; Vilá, Luis M. (Case Reports in Rheumatology, 2022)
Transverse myelitis (TM) is a rare complication seen in 1–2% of patients with systemic lupus erythematosus (SLE). Viral infections may cause TM in these patients by causing a dysregulation of their immune system. We report a 30-year-old woman with SLE who had influenza A and a few days later developed urinary retention, bilateral lower extremity paralysis, upper extremity weakness, and optic nerve and macular edema. Magnetic resonance imaging showed C4-T12 hyperintense lesions consistent with TM. She was treated with intravenous methylprednisolone 1 g daily for 3 days and then 6 cycles of monthly intravenous cyclophosphamide. This treatment was followed by oral prednisone. She had a remarkable clinical response. Visual acuity improved to her baseline, and muscle strength almost fully recovered. Clinicians should be aware that viral infections, including influenza, may induce TM. This case highlights the importance of early recognition and prompt treatment with immunosuppressive drugs in such cases.